Groundwater pollution and emerging environmental challenges of industrial effluent irrigation in Mettupalayam Taluk, Tamil Nadu - Mukherjee, S.; Nelliyat, P. (International Water Management Institute, 2007)
Industrial disposal of effluents on land and the subsequent pollution of groundwater and soil of surrounding farmlands ? is a relatively new area of research. The environmental and socioeconomic aspects of industrial effluent irrigation have not been studied as extensively as domestic sewage based irrigation practices, at least for a developing country like India. The disposal of effluents on land has become a regular practice for some industries. Industries located in Mettupalayam Taluk, Tamil Nadu, dispose their effluents on land, and the farmers of the adjacent farmlands have complained that their shallow open wells get polluted and also the salt content of the soil has started building up slowly. This study attempts to capture the environmental and socioeconomic impacts of industrial effluent irrigation in different industrial locations at Mettupalayam Taluk, Tamil Nadu, through primary surveys and secondary information. This study found that the continuous disposal of industrial effluents on land, which has limited capacity to assimilate the pollution load, has led to groundwater pollution. The quality of groundwater in shallow open wells surrounding the industrial locations has deteriorated, and the application of polluted groundwater for irrigation has resulted in increased salt content of soils. In some locations drinking water wells (deep bore wells) also have a high concentration of salts. Since the farmers had already shifted their cropping pattern to salt-tolerant crops (like jasmine, curry leaf, tobacco, etc.) and substituted their irrigation source from shallow open wells to deep bore wells and/or river water, the impact of pollution on livelihoods was minimized. Since the local administration is supplying drinking water to households, the impact in the domestic sector has been minimized. It has also been noticed that in some locations industries are supplying drinking water to the affected households. However, if the pollution continues unabated it could pose serious problems in the future.